Chromosomální aberace v prenatální diagnostice - výsledky karyotypizace téměř 2000 odběrů plodové vody - Horáček, J; Bečvářová, V; Světnicová, K (Česká gynekologie, 1997)
The frequencies of different types of chromosomal abnormalities are shown in a study performed during 1989 -1996. 32 pathological karyotypes were found, i. e. 1.6 %. The ratio of numerical/structural abnormalities is 1.67. The number of de novo or unexpected structural abnormalities is 67 % from all structural ones in this study. This strongly supports the need of complete cytogenetic analysis.
Keywords: plodová voda; Amniotic Fluid; karyotypizace; ženské pohlaví; Prenatal Diagnosis; Chromosome Aberrations; prenatální diagnóza; Humans; Pregnancy; Karyotyping; Female; těhotenství; lidé; chromozomální aberace